RESPON BEBERAPA KULTIVAR MENTIMUN TERHADAP ZYMV (Zucchini Yellow Mosaic Virus) - U. Sumpena (Universitas Wahid Hasyim, 2012)
U. Sumpena, 2010. Respone of some cucumber cultivars to ZYNV (Zucchini Yellow Mosaic Virus). This experiment was conducted in a screen house in the Subang lowland experimental garden from May to July 2010. Twenty one cultivars of cucumber was tested. Thirty seeds of each cultivar were sown in plastic box containing 1:1 mixture of soil and stable manure. Ten days old seedlings were inoculated mechanically with a ZYMV isolate. None of the cultivars was classified as immune, highly resistance or moderately susceptible. The cultivars tested were classified as moderately resistance (two cultivar namely LV 2908 from Philipina and Hibrida 1 from Indonesia), susceptible (9 cultivars) and highly susceptible (10 cultivars). Key word ; resistence, zymv, cucumber